2015
DOI: 10.1002/hbm.23070
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating unipolar and bipolar depression by alterations in large‐scale brain networks

Abstract: Unipolar and bipolar groups displaying similar symptomatology could be clearly distinguished by characteristic changes in large-scale networks, encouraging further investigation of network fingerprints for clinical use. Hum Brain Mapp 37:808-818, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(55 citation statements)
references
References 58 publications
(82 reference statements)
1
53
1
Order By: Relevance
“…Our primary finding of decreased negative functional connectivity between the DMN and salience networks is supported by previous studies in adults with BD (1620, 57). Our findings are also consistent with studies in PBD that reported increased functional connectivity of the DMN to the insula with higher bipolar index scores (34).…”
Section: Discussionsupporting
confidence: 90%
“…Our primary finding of decreased negative functional connectivity between the DMN and salience networks is supported by previous studies in adults with BD (1620, 57). Our findings are also consistent with studies in PBD that reported increased functional connectivity of the DMN to the insula with higher bipolar index scores (34).…”
Section: Discussionsupporting
confidence: 90%
“…Studies compatible with the hypothesis generally investigated these areas and related networks, finding changes in BD patients that matched the prediction of the model, i.e ., increased strio-anterior cingulate connectivity [24, 32, 48] or decreased cortical-striatal-control [23] in the manic BD phase and 
even in euthymia [25, 29, 53] and in unaffected first-degree relatives [38]. Opposite results were found in depressive phases, with decreased activity in the cingulate [63]. The Yamada model-network was more active in patients with BD compared to those with major depressive disorder [64]; although this is not a strong evidence in favour of the PoM hypothesis, it is indicative.…”
Section: Discussionmentioning
confidence: 99%
“…rumination) in unipolar depression is associated with increased default mode network recruitment and reduced salience network recruitment (30-36). Behavioral, emotional and cognitive dysregulation in bipolar disorder is associated with disrupted salience network recruitment and decreased fronto-parietal executive control network recruitment (37-43). Thus, dysfunction in mood disorders may be associated with inefficient or inflexible switching between processing modes.…”
Section: Introductionmentioning
confidence: 99%